Analisis Kecerdasan emosional, etika kerja Islami dan disiplin kerja terhadap peningkatan kinerja karyawan pada CV Cita Nasional Salatiga dengan komunikasi sebagai variabel moderasi - Khofifah, Nor; Setiawan, Ari (Journal of Management and Digital Business, 2023)
This study aimed to determine the effect of emotional intelligence, Islamic work ethic, and work discipline on employee performance, with communication as a moderating variable. This study uses quantitative research. With a population of employees at CV Cita Nasional Salatiga, the sampling technique in this study used purposive sampling, totaling 55 respondents. The analytical tool used is regression analysis using multiple linear regression. The results of statistical tests show that emotional intelligence, Islamic work ethic, and work discipline have a positive and significant effect on employee performance. Then, partially, emotional intelligence and Islamic work ethic do not affect employee performance, while work discipline has a positive and significant effect on employee performance. Communication can strengthen the influence of emotional intelligence, Islamic work ethic, and work discipline on employee performance.